MUSICAL LITERACY AND EDUCATIONAL PARADIGMS - Alboni Marisa Dudeque Pianovski Vieira; Tadeu Aparecido Malaquias (Editora da Universidade de Santa Cruz do Sul, 2016)
The article presents us contemporary conceptions of musical literacy and its relation to educational paradigmatic issues, thus exposing different types of paradigms and their modifications. The possibility to relate and discuss issues related to these paradigms and to the contributions from different authors to musical literacy issues, characterizing graduates, are also among the objectives of this work. The relevance of these issues is in the few existing debates on the paradigms within music education as well as within the possibility of such a study being able to provide useful material for educators. Of bibliographical and documentary nature, this study is based on the works of Schafer (1992, 1997) and Swanwick (1979, 2003, 2014). The results point to the new trend of musical literacy, with an inclusive commitment, made accessible not only to the student who aims to be a professional musician, but also to people from different social contexts.